Rome and Barbaricum : contributions to the archaeology and history of interaction in European protohistory - Curcă, Roxana-Gabriela; Curcă, Roxana-Gabriela; Rubel, Alexander; Rubel, Alexander; Symonds, R. P.; Symonds, R. P.; Voß, Hans-Ulrich; Voß, Hans-Ulrich (Archaeopress Roman archaeology, 2020)
How did the 'Barbarians' influence Roman culture? What did 'Roman-ness' mean in the context of Empire? What did it mean to be Roman and/or 'Barbarian' in different contexts? Nine papers explore concepts of Romanisation and of Barbaricum from a multi-disciplinary and comparative standpoint, covering Germania, Dacia, Moesia Inferior, Hispania, and more